Effect of fluoxetine on the inhibition of adenylate cyclase activity in foskolin-stumulated MLTC-1 LEYDIG cells - Nguyen Thi Mong Diep; Nguyen Thi Bich Hang; Nguyen Le Cong Minh; Tran Thanh Son; Nguyen Thuy Duong (My University, 2019)
Effect of fluoxetine on the inhibition of adenylate cyclase activity in foskolin-stumulated MLTC-1 LEYDIG cells
Keywords: Fluoxetine; Adenylate cyclase; MLTC-1 cells